DETERMINATION OF COMPETENCE, INDIVIDUAL CARACTERISTICS, EDUCATION AND TRAINING ON SATISFACTION WORKING THROUGH THE PERFORMANCE OF EMPLOYEES IN HR DEVELOPMENT AGENCY KARIMUN DISTRICT - Kurniawan, Ady; Indrayani, Indrayani; Khaddafi, Muammar; Ngaliman, Ngaliman (RADJA PUBLIKA, 2022)
Competency-based HR management is a must, as a paradigm of the approach that is considered the most urgent to emphasize that the human element is the main element of organizational success. However, organizations to be able to provide quality state civil servants in order to support the achievement of the goals and objectives of the organization with high performance standards need to continuously improve the mtu and quality of its human resources. In addition, the competencies possessed by each employee individually can support the implementation of the organization's vision and mission through the strategic performance of government organizations. In this research, the title under study is: Competence Determination, Individual Characteristics, Education and Training on Job Satisfaction through Employee Performance at the Karimun District Human Resources Development Agency.